PARENTAL INVOLVEMENT PADA ORANG TUA DENGAN ANAK SLOW LEARNER DI BANDUNG - Marissa Putri Lutfiatin; Stephani Raihana Hamdan (JURNAL PSIKOLOGI MALAHAYATI, 2021)
ABSTRACT: PARENTAL INVOLVEMENT ON PARENTS OF SLOW LEARNER CHILDREN IN BANDUNG Slow learner is one of students’ characteristics that need special treatment in inclusive schools. The condition of children who are slow to learn has a high enough risk to stay in class. Therefore, the factor of parental involvement in student learning is important for slow learner children's education. The purpose of this research is to give description on how the parental involvement in SDN X. This is a descriptive research with 42 people as population. As a measurement we use Self Assessment of School / Program Parent Involvement Practices Based on Joyce Epstein’s Six Type of Involvement. The result of this research show that 69,05% has a low parental involvement and learning at home aspect has the lowest percentage about 59,52%. Based on these results, it is necessary to increase the involvement of parents with slow learner children, especially in repeating material at home so that the learning achievement of slow learner students can be achieved optimally. Keywords: Inclusive Education, Slow Learner, Parental involvement. Slow learner merupakan salah satu karakteristik siswa yang perlu mendapatkan penanganan khusus di sekolah inklusi. Kondisi anak yang lambat belajar mempunyai resiko cukup tinggi untuk tinggal kelas. Oleh karenanya faktor keterlibatan orang tua dalam pembelajaran siswa menjadi penting bagi pendidikan anak slow learner. Tujuan dari penelitian ini adalah untuk melihat gambaran mengenai parental involvement pada orang tua dengan anak slow learner pada SDN X. Penelitian ini merupakan penelitian deskriptif dengan populasi sebanyak 42 orang. Alat ukur yang digunakan dalam penelitian ini berupa kuesioner Self Assessment of School / Program Parent Involvement Practices berdasarkan teori Joyce Epstein (2001). Hasil penelitian menunjukkan bahwa parental involvement di SDN X termasuk rendah dengan persentase sebesar 69,05% dan aspek yang memiliki persentase tertinggi adalah aspek learning at home dengan persentase sebesar 59,52%. Berdasarkan hasil ini maka perlu adanya upaya peningkatan keterlibatan orang tua dengan anak slow learner khususnya dalam pengulangan materi di rumah agar prestasi belajar siswa slow learner dapat tercapai optimal.    Kata Kunci: Pendidikan Inklusi, Slow Learner, Parental Involvement